Embryonic arsenic exposure triggers long-term behavioral impairment with metabolite alterations in zebrafish - Abu Bakar, Noraini; Wan Ibrahim, Wan Norhamidah; Che Abdullah, Che Azurahanim; Ramlan, Nurul Farhana; Shaari, Khozirah; Shohaimi, Shamarina; Mediani, Ahmed; Nasruddin, Nurrul Shaqinah; Kim, Cheol Hee; Mohd Faudzi, Siti Munirah (Multidisciplinary Digital Publishing Institute, 2022)
Arsenic trioxide (As2O3) is a ubiquitous heavy metal in the environment. Exposure to this toxin at low concentrations is unremarkable in developing organisms. Nevertheless, understanding the underlying mechanism of its long-term adverse effects remains a challenge. In this study, embryos were initially exposed to As2O3 from gastrulation to hatching under semi-static conditions. Results showed dose-dependent increased mortality, with exposure to 30–40 µM As2O3 significantly reducing tail-coiling and heart rate at early larval stages. Surviving larvae after 30 µM As2O3 exposure showed deficits in motor behavior without impairment of anxiety-like responses at 6 dpf and a slight impairment in color preference behavior at 11 dpf, which was later evident in adulthood. As2O3 also altered locomotor function, with a loss of directional and color preference in adult zebrafish, which correlated with changes in transcriptional regulation of adsl, shank3a, and tsc1b genes. During these processes, As2O3 mainly induced metabolic changes in lipids, particularly arachidonic acid, docosahexaenoic acid, prostaglandin, and sphinganine-1-phosphate in the post-hatching period of zebrafish. Overall, this study provides new insight into the potential mechanism of arsenic toxicity leading to long-term learning impairment in zebrafish and may benefit future risk assessments of other environmental toxins of concern.